Macroeconomic responses to an independent monetary policy shock: A (more) agnostic identification procedure - Marco Capasso; Alessio Moneta (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2016)
This study investigates the effects of a monetary policy shock on real output and prices, by means of a novel distribution-free nonrecursive identification scheme for structural vector autoregressions. Structural shocks are assumed to be mutually independent. The identification procedure is agnostic in Uhlig [2005]'s sense, since the response of output to a monetary shock is not restricted. Moreover, assuming mutual independence of the shocks allows us to impose no additional constraints derived from economic theory.
Keywords: C14; C18; C38; C51; E52; 330; Structural Models; Vector Autoregressions; Independent Component Analysis; Identification; Monetary Policy